2014
DOI: 10.4103/0973-1075.125551
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and comparison of salivary secretory leukocyte protease inhibitor in human immunodeficiency virus patients and healthy individuals

Abstract: Aim:Transmission of human immunodeficiency virus (HIV) in the oral cavity is a rare event, despite detectable virus in saliva and oropharyngeal tissues of infected persons, unlike other mucosal sites. Secretory leukocyte protease inhibitor (SLPI) has been suggested as the main soluble factor responsible for the HIV inhibitory effect of saliva. The study was designed to estimate and compare the salivary SLPI levels in HIV patients and healthy controls. Furthermore, the relationship between salivary SLPI levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…29-33 However, other studies have indicated that HIV-1 infection may increase salivary SLPI. 40,41 For these reasons, in the current study we chose to investigate SLPI levels in an HIV + cohort to reduce potential confounding. Moreover, this cohort is far more afflicted by precancerous anal lesions and anal cancer, which was the focus of this study.…”
Section: Discussionmentioning
confidence: 99%
“…29-33 However, other studies have indicated that HIV-1 infection may increase salivary SLPI. 40,41 For these reasons, in the current study we chose to investigate SLPI levels in an HIV + cohort to reduce potential confounding. Moreover, this cohort is far more afflicted by precancerous anal lesions and anal cancer, which was the focus of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Дані щодо рівня SLPI при різних захворюваннях за наявності вірусної інфекції є суперечнимипосилення його рівня в слині спостерігалось у хворих з ВІЛ-інфекцією [19] і зниження експресії SLPI в Епштейна-Барр-позитивних клітинах тканин у онкологічних пацієнтів [25]. Отже, значимість інгібіторів у регуляції внутрішньоклітинного протеолізу при розвитку патологічних процесів, в тому числі в нирці, залишається до кінця не розкритою.…”
Section: вступunclassified
“…[3] Initially studied for its role in the prevention of HIV transmission in saliva, SLPI has recently been recognized as a potential diagnostic and prognostic marker in the head-and-neck cancer. [4] It is found in most secretions of the body and mainly in saliva. [5] Previous research on SLPI has used brush biopsy specimens in OPMD and OSCC.…”
Section: Introductionmentioning
confidence: 99%